Fish and Sclerochronology Research in the Mediterranean: Challenges and Opportunities for Reconstructing Environmental Changes - Matić-Skoko, Sanja; Peharda, Melita; Vrdoljak, Dario; Uvanović, Hana; Markulin, Krešimir (Frontiers in Marine Science, 2020)
Over the past two decades, the field of sclerochronology has been rapidly developing, with scientists devoting significant efforts to studying the physical and chemical variations in hard tissues of aquatic organisms. Most of this research has been limited to certain taxa and geographic areas. Although growth increments in fish otoliths are used for sclerochronology purposes, relatively little has been done in the Mediterranean Sea. According to the literature, the chemical composition of otoliths from Mediterranean fish species has primarily been used for analyzing migration patterns, habitat use, and population structure of commercially important fish species. To the best of our knowledge, there are no studies on fish growth chronology construction conducted in the Mediterranean Sea. In order to identify the opportunities for sclerochronology research on fish from the Mediterranean, we used FishBase to identify potential candidate species with a sufficiently long lifespan and clearly defined growth increments for growth chronology construction and otolith chemistry research. We also present the challenges and limitations for sclerochronology research, including: (i) very few fish species in the Mediterranean Sea have a longevity of several decades; (ii) issues associated with reliable age determination for certain long-lived fish species; (iii) a general lack of understanding and effort to constructed and manage otolith collections; and (iv) limitations imposed by the availability of funding, expertise, and instrumentation. Despite these challenges, fish sclerochronology research has strong potential in the Mediterranean and adjacent seas. Recent studies in the Adriatic Sea have resulted in the construction of bivalve chronologies and the geochemical analysis of shells, providing important time-series data for comparative analysis and a multispecies approach. Furthermore, studies conducted in other parts of the world have demonstrated great potential for the use of fish otoliths in monitoring environmental variability and the effects of pollutants and disturbance.